Concepções pedagógicas de professores de ciências e biologia em escolas públicas de Goiânia – GO: a pedagogia da realidade e a fragilidade das raízes - Peixoto, Dezyrê Mendes (2018)
In this research, we approached Pedagogical Conceptions that are manifested in practice and Brazilian pedagogical ideology, considering that they are based on socio-historical, philosophical, political and economic movements, and that they express the temporality of the thoughts in the educational field. The main objective of this study was to analyze the discourse and the action of teachers of Science and Biology, temporary and effective in Goiânia, and its relation with the initial formation of these teachers. The qualitative approach was adequate to the objectives and given the specificity of the reality in research and the subjects involved, the research was developed through a case study. The data were collected with the teachers, using questionnaire, interview and observation, as well as documentary analysis, regarding documents from different periods. For the data treatment, content analysis and triangulation were used. The study points out that teachers act in a complex and contradictory reality, with little radicality and objectivity in relation to the Pedagogical Conceptions. The pedagogical practice of these teachers is influenced by current educational policies, and their training has given priority to the professional biologist to the detriment of the professional teacher. This way, that happens during the school year, is articulated to the knowledge built by the teachers and is expressed by a Pedagogy of its own, that of reality. The roots, understood here as initial formation, seem fragile in terms of the philosophical, epistemological and historical concepts of Pedagogical Conceptions and in relation to the teaching of Science and Biology. The results of this research invite us to discuss and reflect on the weaknesses of teacher education, in the didactic-pedagogical aspect as well as on the working conditions of teachers. They are also an invitation to undergraduate courses, to the teachers of formation, to the teachers of basic education and to the students, to the rescue of the Pedagogical Conceptions and their appropriation, articulated to the history of Science Teaching and the present reality, as an element of resistance and of improvement for Science Education.